Previous lumbar spine fusion increases the risk of dislocation following total hip arthroplasty in patients with hip-spine syndrome: a systematic review and meta-analysis - Huppert, Ashton; Ambrosio, Luca; Nwosu, Kenneth; Pico, Annie; Russo, Fabrizio; Vadalà, Gianluca; Papalia, Rocco; Denaro, Vincenzo (BMC musculoskeletal disorders, 2024)
Background With life expectancy on the rise, there has been an increase in patients with concomitant degenerative hip and spine pathology, defined as hip-spine syndrome (HSS). Patients affected by HSS may require both total hip arthroplasty (THA) and lumbar spinal fusion (LSF), although there is a paucity of data regarding how the sequential timing of these procedures may influence clinical outcomes. This study aims to compare complications and spinopelvic parameters in patients with HSS who underwent either LSF first or THA first. Methods A systematic search of PubMed and Scopus was conducted for randomized and nonrandomized studies investigating complications and spinopelvic parameters in patients with HSS who had undergone THA and LSF. The Methodological Index for Non-Randomized Studies (MINORS) tool was utilized to assess the risk of bias in included studies. Relevant outcomes were pooled for meta-analysis. Results Eleven articles were included in this study. There was a significantly higher THA dislocation rate in patients who had undergone LSF first compared to those who had THA first (OR: 3.17, 95% CI 1.23–8.15, P = 0.02). No significant difference was found in terms of THA aseptic loosening (OR: 0.86; 95% CI 0.32–2.32, p = 0.77) and revision rate (OR: 1.18, 95% CI: 0.53–2.62) between these two groups. Individuals who received THA only showed a significantly lower risk of hip dislocation (OR: 0.14, 95% CI: 0.08–0.25, P < 0.00001) and THA revision (OR: 0.22, 95% CI: 0.14–0.36, P < 0.00001) compared to patients with a previous LSF. Conclusions In HSS patients who underwent both LSF and THA, those who received LSF first displayed an increased risk of hip dislocation after subsequent THA. Additionally, the relative risks of dislocation and revision rate appeared significantly lower in patients who had undergone THA only when compared to THA patients with a history of previous LSF. Due to the impact of LSF on spinopelvic biomechanics, caution must be exercised when performing THA in individuals with instrumented spines. PROSPERO ID CRD42023412447. Level of evidence LL.